Nicosulfuron Sorption Kinetics and Sorption/Desorption on Volcanic Ash-Derived Soils: Proposal of Sorption and Transport Mechanisms - Escudey-Castro, A; Escudey-Castro, A (Elsevier B.V., 2020)
Nicosulfuron sorption/desorption kinetics were studied through batch sorption studies in ten volcanic ash-derived Andisol and Ultisol soils with acidic pH and variable surface charge. Two different kinetic models were used to fit the experimental data: i) Models to establish kinetic parameters (Pseudo-First and Pseudo-Second-Order), and ii) Models to describe solute transport mechanisms of organic compounds on sorbents (Intraparticle Diffusion, Dimensionless Intraparticle, Boyd, and Two-Site Nonequilibrium). Sorption kinetic data best fit the pseudo-second-order model. Application of these models to describe solute transport suggests that underlying mechanisms are complex in all soils due to: i) surface sorption, with mass transfers controlling sorption kinetics across the boundary layer; and ii) pore diffusion (i.e. intraparticle diffusion into macropores and micropores). The Freundlich model explained equilibrium sorption data in all cases (R2 > 0.9979) with Kf values higher than those reported for different class of soils (6.85–16.08 μg1-1/n mL1/n g-1). The hysteresis was significant in all studied soils. The lower sorption rate on Ultisols must be considered in regards to Nicosulfuron leaching potential. © 2019 Elsevier B.V.